Strategies for learning and academic achievement of secondary school students (Dhaka University Journal of Biological Sciences, 2015)
Relationship between learning strategies and academic achievement was studied. In addition, it explored whether there were any differences between high and low achievers, males and females, and science and humanities’ students in using learning strategies. Findings revealed that academic achievement was significantly correlated with academic self‐efficacy, organization, and metacognitive self‐regulation. High achievers differed from low achievers in using organization, and meta‐cognitive self‐regulation. In control of learning beliefs and rehearsal, significant gender differences exited. Science group students significantly differed from humanities students in academic self‐efficacy, elaboration, and critical thinking.Dhaka Univ. J. Biol. Sci. 24(1): 91-97, 2015 (January)